Developing the Cascade Thermal Circuit for the Turbine Unit Operating on Low-Boiling Working Medium Intended for Agricultural Power Engineering - Shubenko, Oleksandr; Malyarenko, Vitaliy; Babak, Mykola; Senetskyi, Oleksandr Volodymyrovych; Sarapin, Volodymyr (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
The modes of operation of the appropriate cogeneration unit of a low power ( 80 kW) whose closed cycle uses a low-boiling working medium have been analyzed. The engineering solution on the improvement of power plant has been suggested. Realization of the two-cascade thermal circuit would allow us to operate mini-heat and power plants (HPP) both during the winter period and in summer provided that the electric power is increased by 20 to 25 kW. The available low-boiling working media for the second cascade were analyzed and those were selected that maximally meet the requirements set to the thermodynamic efficiency, operation performances, ecological safety and the operation reliability. Using the program system developed by the IPMash of the National Academy of Ukraine the team carried out computation investigations of thermal circuits for two-cascade power units. Performances for the power unit operating during the summer period on low-boiling working medium with hot water supply and in the condensation mode have been obtained; the electric efficiency for such modes will be equal on average to 22 % and 27 %, respectively. The computation data for the performances of the second cascade of mini-HPP with the working medium of R-600a were given for 100 % modes and partial modes used for the hot water supply (HWS) that showed the efficiency of the unit operation in the entire loading range. For the regular electric power generation by the cogeneration unit the option of thermal circuit with the parallel mounting of the boiler and the air capacitor at the turbine exhaust duct of the second cascade was calculated that would allow for the operation of the power system in any HWS mode.